Disaster - "Wolfenstein, Martha" (London, 1957)
It is not easy to find out how disaster affect people. In the best of times our observations of human nature are rather rarely intensive or systematic. In the alarm, disorder, pain and grief created by large scale catastrophes, there have been too many more urgent things to do. It is only recently that research teams have been going into the field to interview victims of disasters, and to observe some of the consequences of such events. The present study is based on material collected in this way, mainly from peace-time disasters in the United States.
Keywords: Psychology